2019
DOI: 10.1371/journal.pone.0209692
|View full text |Cite
|
Sign up to set email alerts
|

Bovine epididymal spermatozoa treatment for in vitro fertilization: Heparin accelerates fertilization and enables a reduction in coincubation time

Abstract: This study aimed to establish a protocol for in vitro embryo production using epididymal sperm (EP). Samples were obtained from ejaculated sperm (EJ) and the epididymis of 7 Gir bulls. First, the effect of heparin (+) on the viability, longevity (Experiment 1) and fertilization rates (Experiment 2) of the EP was evaluated. In experiment 2, a pool of EP and EJ sperm (n = 7) was coincubated with cumulus-oocyte complexes (COCs) for 0, 3, 6, 12 and 18 h, and the fertilization rate (FR) was evaluated. A third exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 36 publications
1
6
0
2
Order By: Relevance
“…Previous studies have shown that despite certain differences in the characteristics of epididymal spermatozoa and freshly ejaculated sperm, the former can be effectively used for in vitro fertilization (IVF) and artificial insemination (AI) of farm animals, including pigs [ 4 ], bulls [ 5 ] and stallions [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that despite certain differences in the characteristics of epididymal spermatozoa and freshly ejaculated sperm, the former can be effectively used for in vitro fertilization (IVF) and artificial insemination (AI) of farm animals, including pigs [ 4 ], bulls [ 5 ] and stallions [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…62.3%), cleavage (43.5% vs. 26.6%), and blastocyst (18.1% vs. 10.5%) compared to WC [ 54 ]. In cattle, a better blastocyst rate was also observed (56% vs. 38%) after sperm separation with PG compared to after washing [ 55 ]. Obtaining blastocyst-stage embryos after heterologous IVF of collared peccary sperm and pig oocytes was not feasible, likely due to the species differences and the variations in culture conditions.…”
Section: Discussionmentioning
confidence: 99%
“…After removing the testicle, the sperm is kept in the tail of the testicle, and the sperm is exposed to a fluid at the time of ejaculation [26]. These fluids contain several substances that are an important influence on sperm viability and motility in the female reproductive tract, such as ions, lipids, energy substrates, organic compounds and proteins [32].…”
Section: Discussionmentioning
confidence: 99%